Impact of Neck Disability on Health-Related Quality of Life among Head and Neck Cancer Survivors - Nilsen, Marci L. (Otolaryngol Head Neck Surg, 2019)
OBJECTIVE. Although neck impairment has been described following surgical resection, limited studies have investigated its prevalence in nonsurgical treatment. The purpose of this study is to determine the prevalence and predictors of neck disability following head and neck cancer (HNC) treatment and to explore its association with quality of life (QOL). STUDY DESIGN. Cross-sectional study. SETTING. HNC survivorship clinic. SUBJECTS AND METHODS. We identified 214 survivors who completed treatment ≥1 year prior to evaluation in the clinic. Self-reported neck impairment was measured using the Neck Disability Index. QOL was measured using the University of Washington QOL Questionnaire, with physical and social subscale scores calculated. Regression analysis and trend tests were employed to explore associations. RESULTS. Over half of survivors (54.2%) reported neck disability. The odds of neck disability in survivors who received nonsurgical treatment and those who received surgery plus adjuvant treatment were 3.46 and 4.98 times higher compared to surgery alone (P = .008, P = .004). Survivors who underwent surgery only had higher physical and social QOL than those who received nonsurgical treatment (physical QOL: P < .001, social QOL: P = .023) and those who received surgery plus adjuvant treatment (physical QOL: P <.001, social QOL: P = .039). CONCLUSION. This study revealed a high prevalence of neck disability following nonsurgical treatment. While neck disability is an established sequela of surgical resection, the impact of nonsurgical treatment has gone unrecognized. Early identification and intervention to prevent progression of neck disability are crucial to optimize QOL.